2020
DOI: 10.1055/s-0040-1721400
|View full text |Cite
|
Sign up to set email alerts
|

X-linked Hypophosphatemic Rickets: Awareness, Knowledge, and Practice of Pediatric Endocrinologists in Arab Countries

Abstract: X-linked hypophosphatemic rickets (XLHR) is a genetic disease caused by inactivating pathogenic variants in PHEX, which results in reduced mineralization of bone, teeth, and renal phosphate wasting. XLHR is traditionally treated by phosphate and vitamin D analogs. Recently, burosumab, a recombinant anti-fibroblast growth factor-23 (FGF-23) monoclonal antibody was approved as specific XLHR therapy. We aimed to assess the awareness, knowledge, and management of XLHR among members of the Arab Society for Pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…A recent study included pediatric endocrinologists exclusively and may not reflect the broader image. 20 In the present study, although 88.9% of participants had heard about XLH, their awareness of the symptoms was limited. This may result in a lack of credibility as patients may hesitate to take further advice from nonexpert health care professionals with no in-depth knowledge about XLH.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…A recent study included pediatric endocrinologists exclusively and may not reflect the broader image. 20 In the present study, although 88.9% of participants had heard about XLH, their awareness of the symptoms was limited. This may result in a lack of credibility as patients may hesitate to take further advice from nonexpert health care professionals with no in-depth knowledge about XLH.…”
Section: Discussioncontrasting
confidence: 55%
“…To this end, the present study and that of Deeb et al are valuable needs-assessment exercises for identifying gaps in the knowledge to help in planning education and training activities. 20 The two studies targeted slightly different populations with some overlap and used instruments with different emphases. Thus, their results should be viewed as complementary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surveys by Beshyah et al 2 and Deeb et al 3 have identified the critical educational needs of teams of health professionals caring for patients with XLH and rare bone disorders. Two important questions arise from these surveys:…”
mentioning
confidence: 99%